Pharmacokinetics of Tenofovir Alafenamide With Boosted Protease Inhibitors in Pregnant and Postpartum Women Living With HIV: Results From IMPAACT P1026s. (1st July 2022) - Brooks, Kristina M.; Pinilla, Mauricio; Stek, Alice M.; Shapiro, David E.; Barr, Emily; Febo, Irma L.; Paul, Mary E.; Deville, Jaime G.; George, Kathleen; Knowles, Kevin; Rungruengthanakit, Kittipong; Browning, Renee; et al.
Abstract : Background: Tenofovir alafenamide (TAF) is a key component of HIV treatment, but pharmacokinetic data supporting the use of TAF during pregnancy are limited. In this study, we report pharmacokinetic, safety, and birth outcomes for TAF 25 mg with a boosted protease inhibitor in pregnant women living with HIV. Methods: IMPAACT P1026s was a multicenter, nonrandomized, open-label, phase IV prospective study. Pregnant women living with HIV receiving TAF 25 mg with a boosted protease inhibitor were eligible. Intensive pharmacokinetic assessments were performed during the second and third trimesters and 6–12 weeks postpartum. Maternal and cord blood samples were collected at delivery. Infant washout samples were collected through 5–9 days postbirth. Comparisons of paired pharmacokinetic data between pregnancy and postpartum were made using geometric mean ratios (GMR) [90% confidence intervals (CIs)] and Wilcoxon signed-rank tests with P < 0.10 considered significant. Results: Twenty-nine women were enrolled from the United States (median age 31 years and weight 84.5 kg during the third trimester; 48% Black, 45% Hispanic/Latina). TAF AUCtau did not significantly differ in the second [GMR 0.62 (90% CI: 0.29 to 1.34); P = 0.46] or third trimester [GMR 0.94 (90% CI: 0.63 to 1.39); P = 0.50] vs. postpartum and were comparable with historical data in nonpregnant adults. TAF was only quantifiable in 2/25 maternal delivery samples and below the limit of quantification in all cord blood and infant washout samples, likely because of the short half-life of TAF. Conclusion: TAF AUCtau did not significantly differ between pregnancy and postpartum. These findings provide reassurance as TAF use during pregnancy continues to expand.